2006
DOI: 10.1007/11945529_2
|View full text |Cite
|
Sign up to set email alerts
|

In Search of the Holy Grail: Looking for the Weakest Failure Detector for Wait-Free Set Agreement

Abstract: Asynchronous failure detector-based set agreement algorithms proposed so far assume that all the processes participate in the algorithm. This means that (at least) the processes that do not crash propose a value and consequently execute the algorithm. It follows that these algorithms can block forever (preventing the correct processes from terminating) when there are correct processes that do not participate in the algorithm. This paper investigates the wait-free set agreement problem, i.e., the case where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…Several papers have been devoted to determine the weakest failure detector to solve the set-agreement problem in a distributed system where any number of processes can fail by crashing [7,8,9,10]. In particular, Zieliński proved recently that anti-Ω -a failure detector that outputs id's of processes such that the id of at least one correct process is output only finitely many times -is the weakest failure detector for set-agreement in a shared memory system [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several papers have been devoted to determine the weakest failure detector to solve the set-agreement problem in a distributed system where any number of processes can fail by crashing [7,8,9,10]. In particular, Zieliński proved recently that anti-Ω -a failure detector that outputs id's of processes such that the id of at least one correct process is output only finitely many times -is the weakest failure detector for set-agreement in a shared memory system [10].…”
Section: Introductionmentioning
confidence: 99%
“…This failure detector has been proposed independently in [11] and [23]. It is used in [11] to boost an obstruction-free object implementation into a non-blocking implementation and it is also shown that this failure detector is the weakest that allows such a boosting.…”
Section: Lemma 4 No Two Processes Decide Different Valuesmentioning
confidence: 99%
“…It is used in [11] to boost an obstruction-free object implementation into a non-blocking implementation and it is also shown that this failure detector is the weakest that allows such a boosting. It is used in [23] to solve the k-set agreement problem when the participating processes can be any subset of processes.…”
Section: Lemma 4 No Two Processes Decide Different Valuesmentioning
confidence: 99%
“…We use the very existence of our algorithm to (a) disprove the conjecture of [14] about the weakest failure detector to implement n-resilient n-set agreement and (b) prove that implementing n-resilient n-set agreement with read/write objects is strictly weaker than solving n + 1-process consensus using n-process consensus.…”
Section: Introductionmentioning
confidence: 96%
“…Failure detector Ω n was shown to be sufficient to solve (1) n-resilient n-setagreement among n + 1 processes using registers [13], and (2) n + 1-process consensus using n-process consensus [16]. In fact, Ω n was also shown to be necessary to implement n + 1-process consensus using n-process consensus [9] and conjectured to be necessary to solve set-agreement [14]. It was our long quest to prove this conjecture that led us identify Υ and devise our set-agreement algorithm based on this oracle.…”
Section: Introductionmentioning
confidence: 99%